Biomechanical characteristics of swing techniques using different clubs in college male golfers - Heng Liu; Zhenjun Li; Hongyu Zhou; Zilong Zhao; Baohua Liu; Zefeng Wang (PLoS ONE, 2025)
Background Golf is a sophisticated sport that integrates precision, skillfulness, and strategic thinking, with swing techniques of different clubs exhibiting distinct biomechanical characteristics. This study aims to investigate the biomechanical characteristics of golfers’ full swings with different clubs from kinematic and dynamics perspectives, thereby providing insights for optimizing full swing techniques. Methods Ten low-handicap right-handed college male golfers were recruited, and their full swing parameters with the driver, 5-iron, and 7-iron (each club was successfully collected 10 times) were synchronously collected using a 250 Hz infrared motion capture system and a 1000 Hz three-dimensional force platform. A one-way ANOVA was conducted to compare biomechanical indicators during the swing motion across different clubs. Results There were significant kinematic differences between the driver and irons, yet smaller differences between 5-iron and 7-iron. As a whole, irons showed a faster peak time and a smaller angular velocity. The GRF of different clubs exhibited different dynamic characteristics at various swing moments, yet the dynamic regularity remained consistent throughout the full swing. During the downswing, the horizontal angular impulse of the driver was greater than irons, and the frontal angular impulse of the 5-iron was greater than that of both driver and 7-iron. Conclusions The characteristics of the driver are slow – paced energy accumulation, delayed acceleration, and horizontal sweeping shots; the characteristics of the 5-iron are that the leading arm coordinates with the frontal angular impulse to optimize the shot trajectory; the characteristics of the 7-iron are compact transition and precise shots driven by the torso.